APLIKASI PROBIOTIK PADA MEDIA PEMELIHARAAN TERHADAP PERTUMBUHAN DAN SINTASAN IKAN NILA MERAH (Oreochromis sp.) - Sumule, Julian Ferdynan; Tobigo, Desiana Trisnawati; Rusaini, Rusaini (FAPETKAN UNTAD, 2017)
Red tilapia (Oreochromis sp.) has been widely cultured throughout the world. Red tilapia is generally cultured in intensive system to increase production. However, many problems could be aroused from intensive culture including deterioration of water quality and fish health. Probiotics can be applied to overcome these problems. Probiotics contain beneficial microbes that can decompose metabolic products and stimulate the cellullar immune responses, thus enhancing the health and the growth of the fish and maintaining the quality of the water in ponds. The study aims to determine the effect of probiotics on the growth and survival of the red tilapia (Oreochromis sp.). The study was designed in a completely randomized design (CRD), which consisted of 4 treatments and 5 replicates. The treatment consisted of treatment A (control) without probiotics, treatment B (0.01 mL of probiotics / 30 L of water), treatment C (0.1 mL / 30 L), and treatment D (1.0 mL / 30 L). Analysis of variance (ANOVA) showed that administration of probiotics with different concentrations in the cultured medium had a high significant effect on the absolute growth of the red tilapia (P<0.01). The highest absolute growth (8,94 g) and survival rate (84%) were found in cultured media with probiotic dose of 1.0 mL / 30 L of water media.Keywords: Red tilapia, probiotics, growth, survival rate.